2022
DOI: 10.3389/fimmu.2022.866373
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Arginine pathway and altered maturation of pleural macrophages in Th2-deficient mice during Litomosoides sigmodontis filarial infection

Abstract: Filarial parasites are tissue dwelling worms transmitted by hematophagous vectors. Understanding the mechanisms regulating microfilariae (the parasite offspring) development is a prerequisite for controlling transmission in filarial infections. Th2 immune responses are key for building efficient anti-parasite responses but have been shown to also lead to detrimental tissue damage in the presence of microfilariae. Litomosoides sigmodontis, a rodent filaria residing in the pleural cavity was therefore used to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…In the context of filarial infections, the local proliferation of AAMs was previously associated with infection control ( 14 ). However, this might be attributable to the tissue studied rather than a helminth-specific difference, as with the same parasite, L. sigmodonti s, it was found that alveolar macrophages are expanded through monocyte recruitment, as in the case of N. brasiliensis ( 26 ).…”
Section: Evidence For Myeloid Cell Killing and Control Of Infectionmentioning
confidence: 98%
“…In the context of filarial infections, the local proliferation of AAMs was previously associated with infection control ( 14 ). However, this might be attributable to the tissue studied rather than a helminth-specific difference, as with the same parasite, L. sigmodonti s, it was found that alveolar macrophages are expanded through monocyte recruitment, as in the case of N. brasiliensis ( 26 ).…”
Section: Evidence For Myeloid Cell Killing and Control Of Infectionmentioning
confidence: 98%